Analysis of Language Style in the Song Atouna El-Toufoule: A Stylistic Study - Masyitoh, Siti; Mutmainah , Mia; Nafi’ah, Khotimatun; Haniefa, Rifda; CH, Hendrawanto (Inspirasi : Jurnal Pendidikan dan Kebudayaan, 2025)
The song Atouna el-Toufoule  popularized by Remi Bandali is a symbol of resistance and an expression of the pain of children who are victims of war. This study aims to reveal how the style of language in the song Atouna el-Toufoule  is used by the author as a form of artistic expression as well as social criticism. This study is a qualitative study with a descriptive analysis method. This study uses the theory of five levels of stylistic analysis by Syihabuddin Qalyubi. The results of this study include language styles based on the level of stylistic analysis, including: 1) al-mustawa al-sauti: repetition of the sounds kasrah and sukun at the end of a sentence, sawamit anfiyah (mim), sawamit infijariyah (ta marbuthah); 2) al-mustawa as-sharfi: use of the isim maf'ul form and writing words that do not comply with the rules of rasm; 3) al-mustawa al-nahwi: al-tikrar, istifham which deviates from its original meaning, 4) mustawa al-dalali: al-dalalah mu'jamiyah, al-dalalah siyaqiyah and also taraduf; 5) al-mustawa al-suwari: the use of tasybih, majaz, and harf nida